PERFORMANCE-BASED REWARD SYSTEM AND ORGANIZATIONAL AGILITY IN THE BANKING INDUSTRY IN NIGERIA (Malaysian Management Journal, 2024)
As organizations strive to maintain a competitive edge, the need for a more agile workforce has become increasingly apparent. Performance-based reward systems have emerged as a powerful tool to facilitate this transformation, by aligning employee motivation with the organization’s strategic goals. However, the overemphasis on individual performance metrics may inadvertently promote unhealthy competition and undermine collaboration. Hence this study examines the effect of performance-based reward system on organizational agility in the banking industry. Specifically, the study seeks to determine how competence-based reward system will affect organizational agility; to examine the impact of reward and incentives on organizational agility. The study has adopted a survey research design to obtain data from a population of 221 staff members of the Guarantee Trust Bank (GTB), which represent the broader banking industry in Nigeria. A sample of 142 was drawn through Taro Yamane and sampled randomly. The study used primary data and questionnaires. Multiple regression was used to test the hypotheses. The study found that organizational agility was affected by the competence-based reward system; and incentive and reward proxy by continuous improvement incentives, teamwork reward, and balancing reward objectives determines the organizational agility of the GTB and the broader banking industry in the country. In conclusion, the performance-based reward system has a significant effect on organizational agility in the banking industry in Nigeria. Thus, the study recommends that banks and other financial organizations should adopt the following aspects of a competence- based reward system such as continuous learning, cross-functional collaboration, and skill development as a strategy for achieving a high level of organizational agility in the GTB through its employees.